Remarkable journey on sustainable tourism destinations; case study on Bintan resort’s award winning on sustainable tourism destination - Amalia, Eva; Lubis, Arina Lutfini (CV. Austronesia Akademika, 2024)
Bintan Resorts awarded the Certificate of Sustainable Tourism Destinations (2022–2025), has demonstrated a significant journey from its establishment to its current position as a leader in sustainable tourism. This research aims to explore the initiatives undertaken by Bintan Resorts in developing a sustainable tourism concept that balances environmental, economic, and socio-cultural aspects. The study elaborates on the best practices and learning experiences from Bintan Resorts’ efforts to achieve sustainable development, which considers the current and future economic, social, and environmental impacts. These initiatives address the needs of visitors, the tourism industry, the environment, and host communities. This study employs a qualitative descriptive approach through field observations, interviews with key stakeholders, and documentation analysis. The research findings reveal both achievements and challenges in implementing sustainability, including the need for stronger policies, stakeholder participation, and the adoption of sustainable practices within a complex system. Bintan Resorts exemplifies a well-executed development scenario that prioritizes sustainability through its blueprint and roadmap. The resort has contributed to economic growth, community empowerment, job creation, and environmental conservation. By employing biodiversity-sensitive approaches and integrating sustainability into all operations, Bintan Resorts has proven that resort development can protect and conserve fragile environments while simultaneously contributing to local, regional, and national economies. This case study highlights how thoughtful design, and planning can successfully align tourism development with environmental protection, societal benefits, and economic progress.